Probing the role of Coniferin and Tetrahydrocurcumin from Traditional Chinese medicine against PSAT1 in early-stage ovarian cancer: An in silico study. - Jia Zhang; Shalesh Gangwar; Nagmi Bano; Shaban Ahmad; Mohammed S Alqahtani; Khalid Raza (PLoS ONE)
Ovarian cancer, a formidable gynaecological malignancy, poses a significant global health challenge, and it is characterised by late-stage diagnosis and a high mortality rate. Even in its early stages, when treatment choices are scarce, ovarian cancer is still a complicated cancer to treat. In this work, we used computational approaches to find putative Traditional Chinese Medicine (TCM) inhibitors that target Phosphoserine Aminotransferase 1 (PSAT1), a crucial enzyme linked to the development of early-stage ovarian cancer. Using a methodical screening approach, we chose a panel of TCM compounds and prepared them, expected to interact with PSAT1. We next evaluated the binding affinities using molecular docking, which helped to identify Coniferin and Tetrahydrocurcumin compounds as potent inhibitors with the docking score of -8.8 kcal/mol and -8.9 Kcal/mol, respectively, and compared to the native ligand. The inhibitory effects of Coniferin and Tetrahydrocurcumin compounds were evaluated with the Pharmacokinetic studies and compared with the standard values, which resulted in an utter performance against each descriptor of the QikProp and performed the Molecular Interaction Fingerprints that resulted in the most interaction residues with counts were 4GLY, 4ASN, 4HIE, 4SER, 4THR, 3ARG and many more. Further, 100ns MD Simulation was performed in neutralised water, resulting in entirely stable deviations, fluctuations, and many intermolecular interactions, and the MM\GBSA studies on all 1000 trajectories have supported the complex's stability. The computational studies have shown a completely stable performance that supports Coniferin, and Tetrahydrocurcumin can be a potent inhibitor of PSAT1. However, further experimental works are needed to confirm this study.